2013
DOI: 10.2298/vsp1303267s
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to depot versus oral antipsychotic medication in schizophrenic patients during the long-term therapy

Abstract: Schizophrenic patients on classical depot antipsychotic maintenance therapy might present subpopulation of patients with significantly longer illness duration, more favorable medication attitude and outcome in relation to those on oral antipsychotics alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Interestingly, there is little data on the application of the MARS on patients receiving LAA. One study showed a positive correlation between receiving long acting fluphenazine and the MARS score [17] which agrees with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, there is little data on the application of the MARS on patients receiving LAA. One study showed a positive correlation between receiving long acting fluphenazine and the MARS score [17] which agrees with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…2017a, 2017b, 2017c; Remington & Khramov 2001; Song et al . 2019; Stanković & Ille 2013; Taipale et al . 2018; Tiihonen et al .…”
Section: Resultsmentioning
confidence: 99%
“…The true effect in 95% of all comparable populations fell within the prediction interval 0.16-23.50 (see supplemental materials). Furthermore, three studies (Joshi et al 2018b;Rosenheck et al 2011;Stankovi c & Ille 2013) found no differences in mean scores on the DAI (n = 1075, 95% CI = À0.399 to 2.731, P = 0.144; s 2 = 1.876, I 2 = 98.89%, Q = 180.473, df = 2, P < 0.001).…”
Section: Medication Adherencementioning
confidence: 95%
“…Long-acting antipsychotics 19,24 Clients on long-acting depot injections may have a more favorable medication attitude and outcome.…”
Section: Non-therapy-based Strategiesmentioning
confidence: 99%